THE CONCEPT OF "HOUSING", ITS HISTORICAL, SCIENTIFIC-THEORETICAL AND LEGAL ASPECTS - Sokhibjanovich, Shukurov Umid (Journal of Learning on History and Social Sciences, 2025)
Objective: The objective of this study is to analyze the concept of "housing" through its historical, scientific-theoretical, and legal dimensions, with a focus on its socio-historical development and its interpretation within housing legislation. Method: The research employs a multidisciplinary approach, combining historical analysis, a review of legal frameworks, and theoretical perspectives from relevant scientific literature to provide a comprehensive understanding of housing as a socio-legal phenomenon. Results: The findings highlight the evolution of housing as a concept influenced by social, cultural, and economic factors, demonstrating its centrality to human welfare and legal systems. The study further identifies critical gaps and ambiguities in housing legislation and offers analytical insights into the implications of these shortcomings. Novelty: This work contributes to the academic discourse by synthesizing diverse perspectives on housing and proposing a unified framework for its conceptualization, emphasizing its dual role as both a human right and a legal construct. The study provides actionable recommendations for enhancing housing policies and legislative clarity, aligning them with contemporary societal needs.